1955
DOI: 10.1083/jcb.1.1.17
|View full text |Cite
|
Sign up to set email alerts
|

A Microphotometric Study of the Syntheses of Desoxyribonucleic Acid and Nuclear Histone

Abstract: 1. The fast green stain of Alfert and Geschwind for nuclear basic protein is shown to obey the Beer-Lambert laws when used on purified histone. Interference from acid substances other than nucleic acids as a possible source of error is indicated. 2. Use of this technique after a modified Feulgen stain enables determination of relative amounts of desoxyribonucleic acid and histone in the same individual cells. 3. DNA and histone are shown to have the same distribution in formalin-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

1955
1955
1981
1981

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(48 citation statements)
references
References 18 publications
3
45
0
Order By: Relevance
“…Microspectrophotometric data indicate that the histone and basic nuclear protein fractions stainable with alkaline fast green (2) or Sakaguchi's reagent increase simultaneously with DNA content (1,6,19,32,56). The increase, however, does not necessarily imply histone synthesis, but might be accounted for by the complexing of previously synthesized histone with DNA of the nucleus, the DNA-histone complex rendering the previously synthesized histone stainable (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microspectrophotometric data indicate that the histone and basic nuclear protein fractions stainable with alkaline fast green (2) or Sakaguchi's reagent increase simultaneously with DNA content (1,6,19,32,56). The increase, however, does not necessarily imply histone synthesis, but might be accounted for by the complexing of previously synthesized histone with DNA of the nucleus, the DNA-histone complex rendering the previously synthesized histone stainable (7).…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of nuclear protein has been studied by means of microspectrophotometry (1,6,19,32,56), interferometry (30,45), radioautography (15,23,51,56), and isotope tracer techniques (12,22,54). The results of such experiments indicate that syntheses of various nuclear protein fractions occur during different stages of the cell cycle.…”
mentioning
confidence: 99%
“…Such analyses of DNA, using Feulgen and methyl green staining and ultraviolet absorption, and of histone, by employing fast green under alkaline conditions, have demonstrated a doubling in amounts of both substances during an interphase period prior to cell division (44,47,19,34,17,8,2). Furthermore the increase in these substances occurs simultaneously during this period (8,2). Relatively little is known, however, of possible qualitative changes in the chromosomal components and their interassociations during the different stages of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigations of the chromosomal components, desoxyribonucleic acid (DNA) and histone, suggest that both substances occur in relatively constant amounts in non-proliferating ceils of diploid tissues (10,30,44,12,4,8,2). While in the case of DNA this constancy per genome appears to hold for all such ceils within a species, differences in amounts and composition of histone among various tissues of the same organism (43,4,13) suggest that a histone constancy may hold only for cells of the same type.…”
Section: Introductionmentioning
confidence: 99%
“…Histochemical and biochemical studies of DNA and histone indicate that these two substances are bound together by ionic bonds (15) and are in constant proportion to each other (1,2,26). Bloch and Godman (2) have suggested that this proportionality is maintained by simultaneous proportional synthesis of histone and DNA.…”
Section: Introductionmentioning
confidence: 99%